Walking a tightrope: Are US state and local governments on a fiscally sustainable path? - Bo Zhao; David Coyne (Federal Reserve Bank of Boston, 2013)
This paper develops a new measure of state and local fiscal sustainability called the "trend gap," which is based on socioeconomic and other fundamental factors and removes the short-term influence of the business cycle. The paper estimates the trend gap and finds that the nationwide per capita trend gap has been on a growing path over the past three decades, a different conclusion than found in previous studies. Social insurance and income maintenance programs have played a major role in the growth of the trend gap, while pension and other post-employment benefits (OPEB) plans have become increasingly important in driving it up. In addition, there are large and growing disparities in the trend gap across states.
Keywords: H4; H7; 330; fiscal sustainability; state and local fiscal trends